Feature of Primary and Secondary Modernization of Tula Region in 2000– 2011 - A. V. Slobozhanin (Vestnik MGIMO-Universiteta)
Modernization, modernization of regions, types of modernization, development of Tula region, industrial and post-industrial development of Russia